2017
DOI: 10.1093/humupd/dmx006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns, foods and nutrients in male fertility parameters and fecundability: a systematic review of observational studies

Abstract: Male adherence to a healthy diet could improve semen quality and fecundability rates. Since observational studies may prove associations but not causation, the associations summarized in the present review need to be confirmed with large prospective cohort studies and especially with well-designed RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
252
3
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 380 publications
(299 citation statements)
references
References 105 publications
6
252
3
7
Order By: Relevance
“…Third, we did not examine the influence of paternal factors, such as diet and lifestyle. There are some reports suggesting that a healthy diet can improve semen quality and fecundability rates in men . Fourth, we obtained information about folate supplement usage but not about its dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not examine the influence of paternal factors, such as diet and lifestyle. There are some reports suggesting that a healthy diet can improve semen quality and fecundability rates in men . Fourth, we obtained information about folate supplement usage but not about its dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the results indicated that healthy diets rich in some nutrients such as omega-3 fatty acids, some antioxidants (vitamin E, vitamin C, β-carotene, selenium, zinc, cryptoxanthin and lycopene), other vitamins (vitamin D and folate) and low in saturated fatty acids and trans -fatty acids were associated with improved reproductive system function. [5] Supplements that have demonstrated positive effects on fertility include aescin, coenzyme Q 10 , glutathione, Korean red ginseng, L-carnitine,…”
Section: Discussionmentioning
confidence: 99%
“…Существует более 25 селенопротеи-нов, таких как гидропероксид фосфолипида ГТП и спер-матозоидный селенопротеин супероксид ГТП, которые помогают поддерживать структурную целостность спер-матозоидов. Морфологические аномалии и нарушение подвижности сперматозоидов являются одними из наи-более распространенных видов патоспермии, связанных с дефицитом селена [18].…”
Section: использование антиоксидантов при ипunclassified